Sperm characteristics of Chukar partridge (Alectoris chukar) breeders as affected by the addition of calcitriol to the semen extender. (3rd April 2019) - Goodarzi, P; Akhlaghi, A; Zamiri, M J; Shirazi, M R Jafarzadeh; Akhlaghi, A A; Habibi, M; Daryabari, H; Saemi, F; Peebles, E D
ABSTRACT: This study was carried out to determine the effect of supplementing the semen extender with calcitriol on in vitro sperm characteristics in Chukar partridges. A total of 60 male Chukar partridges were habituated for semen collection by abdominal massage. Pooled ejaculates from several males were extended (1 to 5 v/v ratio) in the Sexton's diluent containing 0, 24, 48, 96, or 192 μg calcitriol/mL. These concentrations represented 0-, 2-, 4-, 8-, and 16-fold levels of the mean seminal calcitriol concentration, respectively. A total of 12 subsamples from each treatment group were kept at 4 to 5°C or 19 to 24°C for 4, 24, or 48 h. The percentages of motile sperm, live sperm, abnormal sperm, incidence of hypoosmotic swelling (HOS), and thiobarbituric acid reactive species (TBARS) concentrations were determined. The data were analyzed by the xtmixed procedure of STATA software. The percentages of motile sperm, live sperm, abnormal sperm, and seminal TBARS were affected by calcitriol ( P < 0.05). There was no effect of treatments on HOS ( P > 0.05). There was an interaction effect between calcitriol, storage time, and storage temperature on sperm motility, sperm viability, and seminal TBARS. Supplementation of the diluent with 96 μg calcitriol/mL resulted in the highest sperm motility at 4°C. Also, the same treatment group recorded the highest sperm viability and lowest seminal TBARS at 19 to 24°C. Supplementing the diluent with calcitriol had beneficial effects on spermatozoa; however, the fertility rate of spermatozoa extended in calcitriol-supplemented diluent needs to be determined before the procedure can be recommended for use in artificial insemination programs.